Research on the Multi-Dimensional Optimization of Flexible Load under the Dual Carbon Goal - Haijing, Zhang; Jiyan, Liu; Yankun, Feng; Jialu, Zhang; Guangxu, Pan (2025 International Conference on Electrical Drives, Power Electronics & Engineering (EDPEE), 2025)
Under the dual carbon goal, the construction of a new power system has transformed the traditional power grid operation mode towards source load interaction. As an emerging regulatory resource in the power grid, the development of operational mechanisms for adjustable loads under multiple scenarios and factors has important engineering value. Consequently, a multi-dimensional operating mechanism for flexible loads is proposed in this paper. Firstly, the overall idea of the flexible load operation mechanism is analyzed. Secondly, a performance evaluation index system with four dimensions of "observable, measurable, adjustable, and controllable" as the core is constructed under considering factors such as economy, environment, and regulatory technology. Finally, the overall process for evaluating the adjustable load regulation capability is designed.